Diaphragm binder, ceramic diaphragm and secondary battery
By using core-shell structured bottle brush polymer particles as a separator adhesive, the problems of low bonding strength and insufficient heat resistance between the lithium-ion battery separator and electrode sheet are solved, thereby improving the high-temperature stability and safety of the battery.
Patent Information
- Application Number
- CN202411342492.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-07
AI Technical Summary
The existing lithium-ion battery has low bonding strength between the separator and the electrode sheet and poor heat resistance, which makes the battery prone to short circuit at high temperatures. In addition, the cell structure is loose, which affects the safety and reliability of the battery.
Bottle brush polymer particles with a core-shell structure are used as the membrane adhesive. The core layer has a glass transition temperature ≥90℃ and the shell layer has a temperature ≤-10℃. Combined with the bottle brush polymer structure, the heat resistance and adhesion of the membrane are enhanced.
It improves the bonding strength and heat resistance between the separator and the electrode sheet, reduces the thermal shrinkage rate, and enhances the stability and safety of the battery.
Smart Images

Figure BDA0005060099600000111 
Figure BDA0005060099600000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a diaphragm binder, a ceramic diaphragm and a secondary battery. Background Art
[0002] Lithium-ion batteries have been widely used in small mobile portable devices such as smart phones, laptops, power tools, as well as medium and large energy storage equipment such as new energy vehicles, aerospace vehicles, and power stations due to their high energy density, wide operating temperature range, many cycles, and long storage life. Lithium-ion batteries are mainly composed of positive electrodes, negative electrodes, diaphragms, electrolytes, battery shells, etc. Among them, the diaphragm is one of the key inner components. Its main function is to separate the positive and negative electrodes of the battery to prevent the positive and negative electrodes from contacting and short-circuiting. The diaphragms currently used in lithium-ion batteries are generally polyolefin porous membranes. Since the melting point of this polyolefin porous membrane is lower than 200°C, when the battery temperature rises due to internal or external factors, the polyolefin porous membrane will shrink or melt, causing direct contact between the positive and negative electrodes, resulting in a short circuit in the battery, which in turn causes accidents such as battery combustion and explosion.
[0003] In order to increase the energy density of the battery, the compaction density of the positive and negative electrodes has been increased to near the limit. On the one hand, during the charge and discharge cycle, the expansion of the electrode sheet, especially the negative electrode, will cause the battery to deform, seriously affecting the safety and reliability of the battery. On the other hand, as the battery capacity increases, the area, volume and weight of the battery are also increasing. During the battery production process, the loose internal structure of the battery cell and the low mechanical strength often cause the battery cell to deform and become fluffy, and even lead to serious problems such as being unable to enter the shell.
[0004] In order to solve this problem, in recent years, researchers have begun to try to use polymer binders to coat inorganic particles on the surface of the diaphragm substrate to form a composite diaphragm. For example, ceramic particles are coated on the surface of the diaphragm substrate to form a ceramic / polymer composite diaphragm. It is hoped that the heat resistance of the ceramic particles can be used to reduce the thermal shrinkage of the diaphragm. At the same time, the polymer binder can be used to improve the adhesion between the composite diaphragm and the electrode sheet interface, thereby preventing the positive and negative electrodes of the battery from short-circuiting and improving the hardness of the battery cell.
[0005] Therefore, the bonding strength between the composite diaphragm and the electrode sheet interface has a great influence on the hardness of the battery cell. However, so far, the adhesives produced and sold on the market have low bonding strength between the composite diaphragm and the electrode sheet and poor heat resistance. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a diaphragm adhesive, a mixed-coated ceramic diaphragm and a secondary battery. The diaphragm adhesive is bottle brush polymer particles with a core-shell structure, which has the characteristics of high bonding strength and good heat resistance, and can fully meet the application of ceramic diaphragms in batteries.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a diaphragm binder, which is a diblock bottle brush polymer particle with a core-shell structure, wherein the polymer particle comprises a bottle brush-shaped core polymer and a shell polymer; the glass transition temperature of the core polymer is ≥90°C, and the glass transition temperature of the shell polymer is ≤-10°C.
[0009] The diaphragm adhesive of the present invention has a core-shell structure, the core layer has a higher glass transition temperature, which can give the diaphragm adhesive excellent heat resistance; the shell layer has a lower glass transition temperature, which can significantly improve the adhesion of the diaphragm adhesive at room temperature. On this basis, the present invention further introduces a bottle brush polymer structure into the core layer and shell layer of the diaphragm adhesive, which can effectively reduce the thermal shrinkage of the diaphragm and enhance its heat resistance and stability.
[0010] In some preferred embodiments, the glass transition temperature of the core polymer is 100 to 150°C; and the glass transition temperature of the shell polymer is -20 to -50°C.
[0011] Specifically, as some embodiments of the present invention, the glass transition temperature of the core polymer can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, and specific point values between the point values; the glass transition temperature of the shell polymer can be -50°C, -45°C, -40°C, -35°C, -30°C, -25°C, -20°C, and specific point values between the point values; for space considerations, the present invention no longer exhaustively lists the specific point values included in the range.
[0012] In some of the embodiments, the synthetic raw materials of the core polymer include a terminal norbornene group, and the polymer is selected from at least one of styrene, acrylonitrile, acrylamide, acrylic acid, methacrylic acid, and itaconic acid.
[0013] In some embodiments, the raw material for synthesizing the shell polymer includes an acrylic polymer having a norbornene group at the end.
[0014] Specifically, the acrylic polymer is selected from at least one of butyl acrylate, isooctyl acrylate, lauryl methacrylate, ethylene glycol dimethacrylate, hydroxyethyl acrylate, ethyl acetoacetate methacrylate, and methacrylic polyoxyethylene ether.
[0015] Bottle brush polymers (BBPs) are a type of grafted polymers with high density of polymer side chains grafted onto the polymer backbone. Due to the presence of steric hindrance, these polymer side chains repel each other and extend outward, achieving a structure similar to a laboratory flask brush at the molecular level. Bottle brush polymers have the characteristics of low entanglement, extended molecular structure and high molecular weight, showing unique properties different from linear polymers. Studies have shown that different bottle brush polymer structures will greatly affect their performance due to structural parameters such as the density and length of the grafted side chains.
[0016] Bottlebrush polymer is a highly branched macromolecule. In dilute solution, bottlebrush polymer is worm-like. In semi-concentrated solution, when the concentration exceeds the critical value, bottlebrush polymer will grow in one direction to form a liquid crystal structure, and even undergo a crystal conformational transition. Compared with conventional polymers, bottlebrush polymer has better elasticity and can better fit the electrode under the cold pressing process, improving the peel strength.
[0017] There are three methods for synthesizing bottle brush polymers: macromonomer polymerization (Grafting through), direct grafting to the main chain (Grafting to), and grafting from the main chain (Grafting from). Preferably, the present invention adopts macromonomer polymerization (Grafting through) to prepare bottle brush polymers. Specifically, the brush-like core polymer is prepared by macromonomer polymerization using at least one of polystyrene, polyacrylonitrile, polyacrylamide, polyacrylic acid, polymethacrylic acid, and polyitaconic acid with norbornene groups at the end as monomers, and the obtained core polymer has polynorbornene as the main chain skeleton and polystyrene, polyacrylonitrile, polyacrylamide, polyacrylic acid, polymethacrylic acid, and polyitaconic acid as side chains. The bottle brush-like shell polymer is prepared by macromolecular monomer polymerization method using acrylate polymer with norbornene group at the end as monomer. The obtained shell polymer uses polynorbornene as main chain skeleton and uses acrylate polymers such as polybutyl acrylate, polyisooctyl acrylate, polylauryl methacrylate, polyethylene glycol dimethacrylate, polyhydroxyethyl acrylate, polyethyl methacrylate, polymethacrylic polyoxyethylene ether as side chains. The side chain structures of core polymer and shell polymer are different. The core polymer uses polystyrene, polyacrylonitrile, polyacrylamide and polyacrylic acid as side chains, which can control the Tg of the polymer ≥ 90℃, enhance heat resistance and improve cohesive strength; the shell polymer uses acrylate polymer as side chain, which has ester group to improve electrolyte infiltration, and can control the polymer Tg ≤ -10℃, and improve bonding strength.
[0018] In some embodiments, the mass ratio of the core polymer to the shell polymer is 1:(0.1-0.4). Specifically, as some embodiments of the present invention, the mass ratio of the core polymer to the shell polymer is 1:0.1, 1:0.2, 1:0.3, 1:0.4, and specific point values between the point values; for space considerations, the present invention no longer exhaustively lists the specific point values included in the range.
[0019] In some of the embodiments, the molecular weight of the polymerized monomer of the core polymer is 500-5000 Da.
[0020] In some embodiments, the molecular weight of the polymerized monomer of the shell polymer is 500-5000 Da.
[0021] In some of the embodiments, the particle size of the polymer particles is 1-7 μm; specifically, as some embodiments of the present invention, the particle size of the polymer particles is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, and specific point values between the point values; for space considerations, the present invention no longer exhaustively lists the specific point values included in the range.
[0022] The diaphragm binder of the present invention is prepared by the following method:
[0023] (1) dissolving at least one of polystyrene, polyacrylonitrile, polyacrylamide, polyacrylic acid, polymethacrylic acid, and polyitaconic acid having a norbornene group at the end as a monomer or a mixed monomer in an organic solvent, stirring the mixture, adding a Grubbs catalyst in a nitrogen atmosphere to initiate a polymerization reaction, and obtaining a core polymer solution after the polymerization reaction is completed;
[0024] (2) adding an acrylic acid ester polymer having a norbornene group at the end as a monomer to the core polymer solution of step (1), stirring, and continuing the polymerization reaction;
[0025] (3) adding a polymerization inhibitor to the reaction solution of step (2) to terminate the reaction, thereby obtaining diblock bottle brush polymer particles having a core-shell structure, which are the diaphragm binder of the present invention.
[0026] Specifically, in step (1), the organic solvent includes one of xylene and N-methylpyrrolidone.
[0027] Specifically, in step (1), the mass ratio of the organic solvent to the monomer or the mixed monomer is 1:0.15-0.3. Preferably, the mass ratio of the organic solvent to the monomer or the mixed monomer is 1:0.2-0.25.
[0028] Specifically, in step (1), the Grubbs catalyst includes Grubbs first generation catalyst, Grubbs second generation catalyst, Grubbs third generation catalyst, Hoveyda-Grubbs first generation catalyst, and Hoveyda-Grubbs second generation catalyst.
[0029] Specifically, in step (1), the mass ratio of the Grubbs catalyst to the monomer or mixed monomer is 1:10-1000. Preferably, the mass ratio of the Grubbs catalyst to the polymerizable monomer is 1:50-200. More preferably, the mass ratio of the Grubbs catalyst to the polymerizable monomer is 1:100.
[0030] Specifically, in step (1), the reaction time of the polymerization reaction is 5h-7h, and the particle size of the core polymer is 1-5 μm.
[0031] Specifically, in step (1) and step (2), the mass ratio of the monomers is 1:0.1-0.4. Preferably, the mass ratio of the monomers is 1:0.2-0.3.
[0032] Specifically, in step (2), the reaction time of the polymerization reaction is 3h-5h.
[0033] Specifically, in step (3), the inhibitor includes vinyl ethyl ether.
[0034] Specifically, in step (3), the mass ratio of the polymerization inhibitor to the monomer is 1:100-200. Preferably, the mass ratio of the polymerization inhibitor to the monomer is 1:130-180.
[0035] In a second aspect, the present invention provides a ceramic diaphragm slurry, comprising the diaphragm binder and ceramic particles described above.
[0036] In a third aspect, the present invention provides a ceramic diaphragm prepared from the ceramic diaphragm slurry described above.
[0037] In a fourth aspect, the present invention provides a secondary battery comprising the ceramic separator described above.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] The present invention provides a large-particle diaphragm binder, which is a diblock bottle brush polymer particle with a core-shell structure, wherein the polymer particles include a bottle brush-shaped core polymer and a shell polymer; the glass transition temperature of the core polymer is ≥90°C, and the glass transition temperature of the shell polymer is ≤-10°C. The diaphragm binder of the present invention has a core layer with a high glass transition temperature, and the structure of the introduced bottle brush polymer can further effectively reduce the thermal shrinkage of the diaphragm and enhance the heat resistance; the shell layer has a low glass transition temperature, which significantly improves the adhesion at room temperature, and the introduced bottle brush polymer structure has high stability. The diaphragm binder particles of the present invention are relatively large, which solves the problems of small particle size and uneven distribution of the diaphragm material binder particles in the prior art, and improves the performance and stability of lithium-ion batteries; the ceramic diaphragm prepared by the diaphragm binder of the present invention has a low thermal shrinkage rate, and the thermal shrinkage rate of the ceramic diaphragm under 130°C is ≤5%, and there is a strong bonding force between the ceramic diaphragm and the negative electrode plate, and its bonding strength is ≥2N / m. DETAILED DESCRIPTION
[0040] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.
[0041] Example 1
[0042] This embodiment provides a diaphragm adhesive, which is a diblock bottle brush polymer particle with a core-shell structure, wherein the polymer particle comprises a bottle brush-shaped core polymer and a shell polymer; the glass transition temperature of the core polymer is 100°C, and the glass transition temperature of the shell polymer is -20°C.
[0043] The preparation method of the diaphragm binder is as follows:
[0044] (1) 100 parts of polystyrene (molecular weight 1000) with norbornene groups at the end were dissolved in xylene as monomers, stirred evenly, and then 1 part of Grubbs first-generation catalyst was added in a nitrogen atmosphere to initiate the polymerization reaction. The polymerization reaction was completed after 6 hours;
[0045] (2) adding 27 parts of poly(hydroxyethyl acrylate) (molecular weight 1000) having a norbornene group at the end and 3 parts of poly(butyl acrylate) (molecular weight 1000) having a norbornene group at the end to the core polymer solution of step (1), stirring, and continuing the polymerization reaction for 4 hours;
[0046] (3) Adding 1 part of polymerization inhibitor vinyl ethyl ether to the reaction solution of step (2) to terminate the reaction, thereby obtaining diblock bottle brush polymer particles with a core-shell structure and a particle size of 4.1 μm, i.e., a diaphragm binder.
[0047] Example 2
[0048] This embodiment provides a diaphragm adhesive, which is a diblock bottle brush polymer particle with a core-shell structure, wherein the polymer particle comprises a bottle brush-shaped core polymer and a shell polymer; the glass transition temperature of the core polymer is 130°C, and the glass transition temperature of the shell polymer is -30°C.
[0049] The preparation method of the diaphragm binder is as follows:
[0050] (1) 60 parts of polyacrylamide (molecular weight 1000) with norbornene groups at the end and 40 parts of polystyrene (molecular weight 1000) with norbornene groups at the end were dissolved in xylene as monomers, stirred evenly, and then 1 part of Grubbs first-generation catalyst was added in a nitrogen atmosphere to initiate a polymerization reaction. The polymerization reaction was completed after 6 hours;
[0051] (2) 20 parts of poly(hydroxyethyl acrylate) (molecular weight 1000) with norbornene groups at the end and 10 parts of poly(butyl acrylate) (molecular weight 1000) with norbornene groups at the end were added as monomers to the core polymer solution of step (1), stirred, and the polymerization reaction was continued for 4 hours;
[0052] (3) Adding 1 part of polymerization inhibitor vinyl ethyl ether to the reaction solution of step (2) to terminate the reaction, thereby obtaining diblock bottle brush polymer particles with a core-shell structure and a particle size of 4.3 μm, i.e., a diaphragm binder.
[0053] Example 3
[0054] This embodiment provides a diaphragm adhesive, which is a diblock bottle brush polymer particle with a core-shell structure, wherein the polymer particle comprises a bottle brush-shaped core polymer and a shell polymer; the glass transition temperature of the core polymer is 150°C, and the glass transition temperature of the shell polymer is -50°C.
[0055] The preparation method of the diaphragm binder is as follows:
[0056] (1) 95 parts of polyacrylamide (molecular weight 1000) with norbornene groups at the end and 5 parts of polystyrene (molecular weight 1000) with norbornene groups at the end were dissolved in xylene as monomers, stirred evenly, and then 1 part of Grubbs first-generation catalyst was added in a nitrogen atmosphere to initiate the polymerization reaction. The polymerization reaction was completed after 6 hours;
[0057] (2) 25 parts of polybutyl acrylate with norbornene groups at the end and 5 parts of polyhydroxyethyl acrylate with norbornene groups at the end were added as monomers to the core polymer solution of step (1), stirred, and the polymerization reaction was continued for 4 hours;
[0058] (3) Adding 1 part of polymerization inhibitor vinyl ethyl ether to the reaction solution of step (2) to terminate the reaction, thereby obtaining diblock bottle brush polymer particles with a core-shell structure and a particle size of 4.0 μm, i.e., a diaphragm binder.
[0059] Example 4
[0060] This embodiment provides a diaphragm adhesive, which is a diblock bottle brush polymer particle with a core-shell structure, wherein the polymer particle comprises a bottle brush-shaped core polymer and a shell polymer; the glass transition temperature of the core polymer is 170°C, and the glass transition temperature of the shell polymer is -60°C.
[0061] The preparation method of the diaphragm binder is as follows:
[0062] (1) 85 parts of polymethacrylic acid (molecular weight 1000) with norbornene groups at the end and 15 parts of polyacrylamide (molecular weight 1000) with norbornene groups at the end were dissolved in xylene as monomers, stirred evenly, and then 1 part of Grubbs first-generation catalyst was added in a nitrogen atmosphere to initiate a polymerization reaction. The polymerization reaction was completed after 6 hours;
[0063] (2) 15 parts of polybutyl acrylate with a norbornene group at the end and 15 parts of polyisooctyl acrylate with a norbornene group at the end were added as monomers to the core polymer solution of step (1), stirred, and the polymerization reaction was continued for 4 hours;
[0064] (3) Adding 1 part of polymerization inhibitor vinyl ethyl ether to the reaction solution of step (2) to terminate the reaction, thereby obtaining diblock bottle brush polymer particles with a core-shell structure and a particle size of 4.3 μm, i.e., a diaphragm binder.
[0065] Example 5
[0066] This embodiment provides a diaphragm adhesive, which is a diblock bottle brush polymer particle with a core-shell structure, wherein the polymer particle comprises a bottle brush-shaped core polymer and a shell polymer; the glass transition temperature of the core polymer is 170°C, and the glass transition temperature of the shell polymer is -20°C.
[0067] The preparation method of the diaphragm binder is as follows:
[0068] (1) 85 parts of polymethacrylic acid (molecular weight 1000) with norbornene groups at the end and 15 parts of polyacrylamide (molecular weight 1000) with norbornene groups at the end were dissolved in xylene as monomers, stirred evenly, and then 1 part of Grubbs first-generation catalyst was added in a nitrogen atmosphere to initiate a polymerization reaction. The polymerization reaction was completed after 6 hours;
[0069] 27 parts of poly(hydroxyethyl acrylate) (molecular weight 1000) with norbornene groups at the end and 3 parts of poly(butyl acrylate) (molecular weight 1000) with norbornene groups at the end were added to the core polymer solution of step (1), stirred, and the polymerization reaction was continued for 4 hours;
[0070] (3) Adding 1 part of polymerization inhibitor vinyl ethyl ether to the reaction solution of step (2) to terminate the reaction, thereby obtaining diblock bottle brush polymer particles with a core-shell structure and a particle size of 4.2 μm, i.e., a diaphragm binder.
[0071] Example 6
[0072] This embodiment provides a diaphragm adhesive, which is a diblock bottle brush polymer particle with a core-shell structure, wherein the polymer particle comprises a bottle brush-shaped core polymer and a shell polymer; the glass transition temperature of the core polymer is 100°C, and the glass transition temperature of the shell polymer is -60°C.
[0073] The preparation method of the diaphragm binder is as follows:
[0074] (1) 100 parts of polystyrene (molecular weight 1000) with norbornene groups at the end were dissolved in xylene as monomers, stirred evenly, and then 1 part of Grubbs first-generation catalyst was added in a nitrogen atmosphere to initiate the polymerization reaction. The polymerization reaction was completed after 6 hours;
[0075] (2) 15 parts of polybutyl acrylate with a norbornene group at the end and 15 parts of polyisooctyl acrylate with a norbornene group at the end were added as monomers to the core polymer solution of step (1), stirred, and the polymerization reaction was continued for 4 hours;
[0076] (3) Adding 1 part of polymerization inhibitor vinyl ethyl ether to the reaction solution of step (2) to terminate the reaction, thereby obtaining diblock bottle brush polymer particles with a core-shell structure and a particle size of 4.4 μm, i.e., a diaphragm binder.
[0077] Comparative Example 1
[0078] A diaphragm binder, which differs from Example 1 in that the binder is a polymer particle with a non-core-shell structure, obtained by blending a bottle brush polymer with a glass transition temperature of 100°C and a bottle brush polymer with a glass transition temperature of -20°C, and the preparation method is as follows:
[0079] (1) 100 parts of polystyrene (molecular weight 1000) with norbornene groups at the end were dissolved in xylene as monomers, stirred evenly, and then 1 part of Grubbs first-generation catalyst was added in a nitrogen atmosphere to initiate the polymerization reaction. The polymerization reaction was completed after 6 hours;
[0080] (2) 27 parts of poly(hydroxyethyl acrylate) (molecular weight 1000) with a norbornene group at the end and 3 parts of poly(butyl acrylate) (molecular weight 1000) with a norbornene group at the end were dissolved in xylene, stirred evenly, and then 1 part of Grubbs first-generation catalyst was added in a nitrogen atmosphere to initiate the polymerization reaction. The polymerization reaction was completed after 6 hours;
[0081] (3) The bottle brush polymers of step (1) and step (2) are mixed to obtain a non-core-shell structured blended polymer diaphragm adhesive.
[0082] Comparative Example 2
[0083] A membrane binder, the membrane binder is a polymer particle with a core-shell structure, the polymer particle includes a core polymer and a shell polymer; the glass transition temperature of the core polymer is 90°C, and its polymerized monomers include 40 parts of styrene and 10 parts of divinylbenzene, and the glass transition temperature of the shell polymer is -50°C, and its polymerized monomers include a combination of 29.88 parts of butyl acrylate, 0.72 parts of diallyl phthalate, 1.8 parts of acrylic acid and 3.6 parts of lauryl acrylate. For the preparation method of the membrane binder, please refer to Example 1 of Chinese Patent Application 202310578893.7.
[0084] Comparative Example 3
[0085] Conventional PVDF binder is used.
[0086] Application Example 1
[0087] This application example provides a ceramic diaphragm, which includes a polyethylene porous film with a thickness of 7 μm and a ceramic coating with a thickness of 3 μm arranged on the polyethylene porous film, and the materials of the ceramic coating include, by mass: 10 parts of diaphragm binder (Example 1), 82 parts of hydrated alumina, 5 parts of SWA610 ceramic binder, and 1 part of carboxymethyl cellulose.
[0088] Application Examples 2-6 and Comparative Application Examples 1-3
[0089] The difference between Application Examples 2-6 and Comparative Application Examples 1-3 and Application Example 1 is that the diaphragm adhesives of Examples 2-6 and Comparative Examples 1-3 are used respectively.
[0090] The performance test of the ceramic diaphragm provided in the corresponding use case 1-6 and the comparative application example 1-3 is carried out as follows:
[0091] Dry bonding strength test between the diaphragm and the negative electrode sheet: The diaphragm and the graphite negative electrode sheet prepared by the scheme of the present invention were cut into 20×100 mm strips respectively, cold pressed for 20 seconds at room temperature 25°C and 1 MPa, and the bonding strength was tested using an electronic tensile testing machine.
[0092] Wet bonding strength test between the diaphragm and the negative electrode sheet: The diaphragm and the graphite negative electrode sheet prepared by the scheme of the present invention were cut into 20×100 mm strips respectively, cold pressed for 20 seconds at room temperature 25°C and 1 MPa, immersed in 60°C electrolyte for 1 hour, and the bonding strength was tested using an electronic tensile testing machine.
[0093] Diaphragm heat resistance test: stack the diaphragms prepared by the scheme of the present invention into 3 stacks, exhaust the air between the membranes, take out the sample cut into 300mm×100mm, and measure the length A1 of the cut sample. Set the oven temperature to 130℃, and keep it warm for 1h after reaching the temperature. Put the sample in the oven and keep it warm for 1h. After the insulation is completed, take out the diaphragm, cool it for 10min, and measure the length A2 of the sample.
[0094] Diaphragm thermal shrinkage = (A1-A2) / A1×100%
[0095] The test results are shown in Table 1.
[0096] Table 1
[0097] Thermal shrinkage (%) Dry adhesive peel strength (N / m) Wet peel strength (N / m) Application Example 1 1.8 5.4 5.3 Application Example 2 1.3 5.8 4.8 Application Example 3 0.9 6.1 5.7 Application Example 4 1.2 3.5 2.3 Application Example 5 1.1 3.7 3.2 Application Example 6 1.9 4.7 2.5 Comparative application example 1 3.1 1.7 0.4 Comparative Application Example 2 5.2 1.5 0.8 Comparative Application Example 3 3.8 0 0
[0098] From the test results in Table 1, it can be seen that the ceramic diaphragm prepared by using the diaphragm binder of Examples 1-6 has a lower thermal shrinkage rate, and the thermal shrinkage rate of the heat-resistant diaphragm at 130°C is ≤2%, and there is a strong bonding force between the diaphragm and the negative electrode plate, and its dry and wet peel strengths are ≥2N / m. In Examples 4-6, the glass transition temperature of the core polymer is relatively high or the glass transition temperature of the shell polymer is relatively low, and the performance of the resulting ceramic diaphragm is relatively poor. Comparative Example 1 uses a binder obtained by simple blending of polymers with different glass transition temperatures. It does not have a specific core-shell structure, and poor bonding will occur because the high Tg polymer competes with the low Tg polymer for the position of contact with the electrode; the polymer of the binder in Comparative Example 2 does not have a bottle brush structure, and the material density and elasticity are weaker than those in Application Example 1, resulting in heat shrinkage resistance and dry / wet peel strength.
[0099] Battery performance test
[0100] The above-mentioned separator is used to assemble the battery. The basic information of the assembled battery is as follows:
[0101] Preparation of positive electrode sheet: HSV900 and N-methylpyrrolidone were mixed to prepare a binder solution with a mass fraction of 7%, and then 28 parts by weight of N-methylpyrrolidone, 1 part of conductive carbon Super.P and 0.5 parts of conductive graphite KS-6 were added in a double planetary mixer, stirred for 1 hour, 45 parts of the binder solution were added, stirred for 1.5 hours, and 100 parts of lithium iron phosphate active material (DY-3) were added, stirred for 30 minutes, and then the positive electrode slurry was obtained. The positive electrode slurry was then scraped on the carbon-coated aluminum foil and baked at 100°C for 1 minute to obtain a positive electrode sheet;
[0102] Preparation of negative electrode sheet: negative electrode materials graphite, conductive carbon black, sodium carboxymethyl cellulose and styrene butadiene latex are mixed in a mass ratio of 94.5:1:2.25:2.25, deionized water is added to obtain negative electrode slurry, and then the negative electrode slurry is scraped on the surface of copper foil and dried to obtain a negative electrode sheet;
[0103] Preparation of lithium-ion battery: Assemble the above-mentioned positive electrode sheet, negative electrode sheet, electrolyte and separator to obtain a lithium-ion battery.
[0104] The battery performance test method is as follows:
[0105] The test method for 0.5C discharge gram capacity is: charging: 0.5C constant current and constant voltage to 4.2V, 0.05C cut-off; discharging: 0.5C constant current discharge to 3.0V, one cycle.
[0106] The test method of DCIR test is: ① Test temperature: 25℃; ② SOC: 0, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%; ③ DCIR test method: 3C discharge for 30s.
[0107] The test method for 85℃ storage retention rate is: place the battery in an 85℃ oven for 8 hours after fully charging, and then test the capacity after taking it out.
[0108] The cycle performance test method is: charge the battery to 4.5V at a constant current of 6000mA (2C) at 25°C, then charge at a constant voltage with a cut-off current value of 150mA, and then discharge to 3V at a constant current of 6000mA, which is considered one cycle; after repeating 500 times, calculate the capacity remaining rate after the cycle (%) = (discharge capacity after n cycles / first discharge capacity) × 100%.
[0109] Test results are visible;
[0110] Table 2 Test results
[0111]
[0112]
[0113] It can be seen from the test results in the above table that the battery cells prepared using the separator binders of Examples 1-6 have relatively better high-temperature storage performance and relatively better 2C / 2C cycle performance.
[0114] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.
Claims
1. A membrane adhesive, characterized in that: The membrane binder is a diblock bottle brush polymer particle having a core-shell structure, wherein the polymer particle comprises a bottle brush-shaped core polymer and a shell polymer; The glass transition temperature of the core polymer is ≥90°C, and the glass transition temperature of the shell polymer is ≤-10°C.
2. The diaphragm adhesive according to claim 1, characterized in that: The synthetic raw material of the core polymer includes a polymer with a norbornene group at the end, and the polymer is selected from at least one of styrene, acrylonitrile, acrylamide, acrylic acid, methacrylic acid, itaconic acid and the like.
3. The diaphragm adhesive according to claim 1, characterized in that: The synthetic raw materials of the shell polymer include acrylic ester polymers with norbornene groups at the ends.
4. The diaphragm adhesive according to claim 1, characterized in that: The mass ratio of the core polymer to the shell polymer is 1:(0.1-0.4).
5. The diaphragm adhesive according to claim 1, characterized in that: The molecular weight of the polymerized monomer of the core polymer is 1000-5000Da.
6. The diaphragm adhesive according to claim 5, characterized in that: The molecular weight of the polymerized monomer of the shell polymer is 1000-5000 Da.
7. The diaphragm adhesive according to claim 1, characterized in that: The particle size of the polymer particles is 1-7 μm.
8. A ceramic diaphragm slurry, characterized in that: The invention comprises the diaphragm binder and ceramic particles as described in any one of claims 1 to 7.
9. A ceramic diaphragm, characterized in that: Prepared from the ceramic diaphragm slurry as claimed in claim 8.
10. A secondary battery, characterized in that: Comprising the ceramic diaphragm as claimed in claim 9.
Citation Information
Patent Citations
Heat-resistant diaphragm binder as well as preparation method and application thereof
CN116606616A
Cited By
Core-shell structure polymer particle, emulsion containing core-shell structure polymer particle, and preparation method and application of emulsion
CN121427021A
Diaphragm binder as well as preparation method and application thereof
CN122037835A
Composite ceramic coated diaphragm and method for manufacturing the same
CN122782112A